2017
DOI: 10.1016/j.cbpc.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Upregulating Nrf2-dependent antioxidant defenses in Pacific oysters Crassostrea gigas: Investigating the Nrf2/Keap1 pathway in bivalves

Abstract: Analysis of the Pacific oyster Crassostrea gigas annotated genome revealed genes with conserved sequences belonging to typical cap 'n' collar Nrf2 domain, a major player in antioxidant protection, and domains belonging to Nrf2 cytoplasmic repressor (Keap1), but little is known about Nrf2/Keap1 induction in bivalves. C. gigas were exposed to waterborne 10 and 30μM curcumin, a known inducer of the mammalian Nrf2. Curcumin disappeared from the seawater after 10h, and accumulated in the gills (10h) and digestive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Nuclear factor erythroid 2‐related factor 2 (Nrf2) is a critical transcription factor in cellular oxidative stress response (Hui & Yang, 2018). Kelch‐like ECH‐associated protein 1 (Keap1) senses oxidative stress and affects the Nrf2 mRNA expression (Danielli et al, 2017). Keap1‐Nrf2 pathway plays an essential role in activating antioxidative genes (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor erythroid 2‐related factor 2 (Nrf2) is a critical transcription factor in cellular oxidative stress response (Hui & Yang, 2018). Kelch‐like ECH‐associated protein 1 (Keap1) senses oxidative stress and affects the Nrf2 mRNA expression (Danielli et al, 2017). Keap1‐Nrf2 pathway plays an essential role in activating antioxidative genes (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, when the cells are exposed to ROS or electrophile, Nrf2 dissociates from Keap1 and rapidly translocates into the nucleus, and then form a heterodimer with the small Maf protein, which ultimately bind to antioxidant response element (ARE) (Heiss et al, 2013;Ho et al, 2012). Nrf2-Keap1 pathway controls the expression of antioxidant gene include HO-1 (Klaassen & Reisman, 2010), SOD (Zhu et al, 2005(Zhu et al, , 2008, CAT (Zhu et al, 2008), glutathione peroxidase (GPx) (Naidu et al, 2015) and GR (Danielli et al, 2017). In this study, the Nrf2-Keap1 pathway was used to evaluate the effects of different lipid levels on the antioxidant capacity of T. ovatus.…”
mentioning
confidence: 99%
“…However, when the cells are exposed to a hyperoxic environment, the conformation of Keap1 protein changes, preventing it from binding to Nrf2. Nrf2 is then released into the nucleus, expressed extensively, and promotes the expression of downstream antioxidant HO-1, imparting resistance to oxidative damage ( 14 ). Research has further shown that the expression levels of Nrf2, Keap1 and HO-1 are all decreased in the lenses of cataract patients, which indicates that the mechanism of the signaling pathway for antioxidant protection is damaged.…”
Section: Discussionmentioning
confidence: 99%